ORGANISASI DAN MANAJEMEN DALAM ERA EKONOMI GLOBAL - Lisda L. Asi (Jurnal Inovasi, 2010)
Global Economy has become the oft-repeated issues in today's world. Global economy as free trade, involves countries, cross-border trade of goods, services and capitals. Barriers have been remove, protection lessened, subsidies reduced, and unlimited quotas wiped out, in the global economy we assume that free trade is more benefical for all as competitive and comparative adventages turned to account by the concerned parties in the free market or global economy. How ever, the effects of the global economy are the flows of good, services and capitals, but also the increasing challengers for the bisnisman. In this regard, we could see, the burgeoning competitor, emphasis on quality and productivity, as well as organizational re-structuring, job re-drafting and re-orientation toward to the business environment and re- organization in facing the global economy.